Monitoring Gene Expression during a Galleria mellonella Bacterial Infection - Laura Moya-Andérico; Joana Admella; Rodrigo Fernandes; Eduard Torrents (Microorganisms, 2020)
Galleria mellonella larvae are an alternative in vivo model that has been extensively used to study the virulence and pathogenicity of different bacteria due to its practicality and lack of ethical constraints. However, the larvae possess intrinsic autofluorescence that obstructs the use of fluorescent proteins to study bacterial infections, hence better methodologies are needed. Here, we report the construction of a promoter probe vector with bioluminescence expression as well as the optimization of a total bacterial RNA extraction protocol to enhance the monitoring of in vivo infections. By employing the vector to construct different gene promoter fusions, variable gene expression levels were efficiently measured in G. mellonella larvae at various time points during the course of infection and without much manipulation of the larvae. Additionally, our optimized RNA extraction protocol facilitates the study of transcriptional gene levels during an in vivo infection. The proposed methodologies will greatly benefit bacterial infection studies as they can contribute to a better understanding of the in vivo infection processes and pathogen–mammalian host interactions.